2022
DOI: 10.35196/rfm.2021.1.15
|View full text |Cite
|
Sign up to set email alerts
|

GENERACIONES AVANZADAS DE UNA CRUZA DE Solanum lycopersicum × S. habrochaites COMO PORTAINJERTOS DE TOMATE

Abstract: El desarrollo de portainjertos es una importante contribución al mejoramiento del tomate; su uso hace posible conferir caracteres de resistencia sin sacrificar las cualidades agronómicas del germoplasma élite. En el presente estudio se realizó una evaluación agro-morfológica de familias F3 y F4 obtenidas del cruzamiento interespecífico entre las accesiones CP-L-S6 de Solanum lycopersicum y LA1223 de S. habrochaites, con el fin de estudiar su segregación transgresiva e identificar materiales con potencial de po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
0
0
1
Order By: Relevance
“…On the other hand, a high content of total soluble solids is associated with a greater capacity for nutrient absorption or translocation, which is a desirable quality in rootstocks [55]. In this study, it was observed that the ºBrix content was significantly affected by the hybrids, more than by the rootstocks.…”
Section: Fruit Qualitymentioning
confidence: 60%
See 1 more Smart Citation
“…On the other hand, a high content of total soluble solids is associated with a greater capacity for nutrient absorption or translocation, which is a desirable quality in rootstocks [55]. In this study, it was observed that the ºBrix content was significantly affected by the hybrids, more than by the rootstocks.…”
Section: Fruit Qualitymentioning
confidence: 60%
“…However, there are fruits that do not conform to the standard (extra-small) but can be used for industrial purposes. Physiologically, fruit development involves a redirection of assimilate translocation towards reproductive organs [55], which aligns with the findings of previous studies [56], suggesting that rootstocks can promote a greater root volume, providing the stem with greater vigor and the ability to enhance elite fruit yield, as the vigor of pattern influences graft expression [13,57]. On the other hand, Doñas-Ucles et al [58] reported improvements in fruit size in Italian sweet peppers (Palermo/Tresor) using rootstocks during two years of evaluation.…”
Section: Yield Componentsmentioning
confidence: 99%
“…Promedios de los años 2020 y 2021. Una concentración alta de sólidos solubles totales se asocia con mayor capacidad de absorción y transporte de nutrimentos (Cíntora-Martínez et al, 2021), y es el principal componente de calidad para fines nutricionales. Diecinueve de las líneas sobresalientes en rendimiento no difirieron estadísticamente en contenidos de SST con Río Grande.…”
Section: Calidad De Frutounclassified
“…Джерелом унікальних генів для селекції сильнорослих і стійких підщеп помідора є дикорослі види роду Solanum, які використовують у гібридизації із культурним помідором переважно у якості батьківських форм (King et al, 2010). Для створення комерційних підщеп помідора широко використовують такі дикорослі види, як Solanum habrochaites -стійкість до вірусних і грибних хвороб, в т. ч. до фузаріозу (Cíntora-Martínez et al, 2021;Kabaş & Celik, 2021;Vanlay et al, 2022); S. pimpinellifoliumпосухостійкість, стійкість до засолення, фітофторозу і грибів роду Verticillium; S. heesmaniiстійкість до засолення і грибів роду Verticillium; S. neorickii -сіра гниль плодів (Peralta et al, 2005).…”
unclassified